Rapid Ring‐Opening Metathesis Polymerization of Monomers Obtained from Biomass‐Derived Furfuryl Amines and Maleic Anhydride. Issue 11 (17th May 2019) - Blanpain, Anna; Clark, James H.; Farmer, Thomas J.; Guo, Yuanlong; Ingram, Ian D. V.; Kendrick, John E.; Lawrenson, Stefan B.; North, Michael; Rodgers, George; Whitwood, Adrian C.
Abstract: Well‐controlled and extremely rapid ring‐opening metathesis polymerization of unusual oxanorbornene lactam esters by Grubbs third‐generation catalyst is used to prepare a range of bio‐based homo‐ and copolymers. Bio‐derived oxanorbornene lactam monomers were prepared at room temperature from maleic anhydride and secondary furfuryl amines by using a 100 % atom economical, tandem Diels–Alder lactamization reaction, followed by esterification. Several of the resulting homo‐ and copolymers show good control over polymer molecular weight and have narrow molecular weight distributions. Abstract : Sustainable plastics : Bio‐derived oxanorbornene lactam monomers were prepared at room temperature from maleic anhydride and secondary furfuryl amines by using a 100 % atom‐economical, tandem Diels–Alder‐lactamization reaction, followed by esterification. These then underwent well‐controlled and extremely rapid ring‐opening metathesis polymerization with the Grubbs third‐generation catalyst to prepare a range of bio‐based homo‐ and copolymers.